Approximation by q-Post-Widder Operators Based on a New Parameter - Qiu Lin (Abstract and Applied Analysis)
The purpose of this paper is to introduce q-Post–Widder operators based on a new parameter and study their approximation properties. The moments and central moments are investigated. And some local approximation properties of these operators by means of modulus of continuity and Peetre’s K-functional are presented. Furthermore, the rate of convergence for these operators is obtained. Weighted approximation and the quantitative q-Voronovskaja type theorem are discussed. Finally, numerical illustrative examples have been given to show the convergence of these newly defined operators.